2022
DOI: 10.1021/acs.nanolett.1c04124
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Oxidation and Surface Reconstructions on Stepped Cu(100) and Cu(110)

Abstract: How defects such as surface steps affect oxidation, especially initial oxide formation, is critical for nano-oxide applications in catalysis, electronics, and corrosion. We posit that surface reconstruction, a crucial intermediate oxidation step, can highlight initial oxide formation preferences and thus enable bridging the temporal and spatial scale gaps between atomistic simulations and experiments. We investigate the surface-stepinduced uneven surface oxidation on Cu(100) and Cu(110), using atomic-scale in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Upon extended oxygen exposure, the stable overlayer is breached by Cu 2 O islands that nucleate on the surface and grow both horizontally and vertically, which leads to subsurface oxidation. , The transition from MRR is suggested to take place after a critical oxygen exposure . Notably, however, grain boundaries, facet-edges and -corners, and step-edges can decrease the required oxygen exposure and facilitate oxide island nucleation. ,, Apart from the mentioned studies on extended surfaces, we have also reported the oxide island growth by in situ ADF-STEM on similar Cu nanoparticles as investigated here …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Upon extended oxygen exposure, the stable overlayer is breached by Cu 2 O islands that nucleate on the surface and grow both horizontally and vertically, which leads to subsurface oxidation. , The transition from MRR is suggested to take place after a critical oxygen exposure . Notably, however, grain boundaries, facet-edges and -corners, and step-edges can decrease the required oxygen exposure and facilitate oxide island nucleation. ,, Apart from the mentioned studies on extended surfaces, we have also reported the oxide island growth by in situ ADF-STEM on similar Cu nanoparticles as investigated here …”
Section: Resultsmentioning
confidence: 55%
“…37 Notably, however, grain boundaries, facet-edges and -corners, and step-edges can decrease the required oxygen exposure and facilitate oxide island nucleation. 16,29,38 Apart from the mentioned studies on extended surfaces, we have also reported the oxide island growth by in situ ADF-STEM on similar Cu nanoparticles as investigated here. 24 Translating the above to our experimental conditions, it becomes clear that starting from a CO-covered surface and sequentially exposing it to a CO + O 2 reaction gas mixture constitutes significantly different conditions, for which the pathway of the subsurface Cu oxidation has not been as extensively studied.…”
Section: )mentioning
confidence: 78%
See 1 more Smart Citation
“…1b). 2 This (2×1) restructuring is characterized by Cu-O-Cu chains growing preferentially along the [001] direction in every other [110]-(1×1) spacing, as shown by the side and top views of the density-functional theory (DFT)-relaxed structure model in Fig. 1c.…”
mentioning
confidence: 99%
“…The studied surface reconstruction was found to be uneven on stepped surfaces, namely due to step induced O diffusion barrier differences. [1] The second example concerns the oxide growth process. As shown in Figure 2, epitaxial Cu 2 O islands on Cu(100) were observed to grow layer-by-layer along Cu 2 O(110) planes, instead of previously expected Cu 2 O(100) planes, using in situ ETEM.…”
mentioning
confidence: 99%